A note on health insurance under ex post moral hazard - Pierre Picard (Risks, 2016)
In the linear coinsurance problem, examined first by Mossin (1968), a higher absolute risk aversion with respect to wealth in the sense of Arrow-Pratt implies a higher optimal coinsurance rate. We show that this property does not hold for health insurance under ex post moral hazard; i.e., when illness severity cannot be observed by insurers, and policyholders decide on their health expenditures. The optimal coinsurance rate trades off a risk-sharing effect and an incentive effect, both related to risk aversion.
Keywords: D1; D8; I1; 330; health insurance; ex post moral hazard; coinsurance